Safety, tolerability, and efficacy of TEV-48125 for preventive treatment of chronic migraine: a multicentre, randomised, double-blind, placebo-controlled, phase 2b study. Issue 11 (November 2015) - Bigal, Marcelo E; Edvinsson, Lars; Rapoport, Alan M; Lipton, Richard B; Spierings, Egilius L H; Diener, Hans-Christoph; Burstein, Rami; Loupe, Pippa S; Ma, Yuju; Yang, Ronghua; Silberstein, Stephen D
Summary Background Benefits of calcitonin-gene related peptide (CGRP) inhibition have not been established in chronic migraine. Here we assess the safety, tolerability, and efficacy of two doses of TEV-48125, a monoclonal anti-CGRP antibody, in the preventive treatment of chronic migraine. Methods In this multicentre, randomised, double-blind, double-dummy, placebo-controlled, parallel-group phase 2b study, we enrolled men and women (aged 18–65 years) from 62 sites in the USA who had chronic migraine. Using a randomisation list generated by a central computerised system and an interactive web response system, we randomly assigned patients (1:1:1, stratified by sex and use of concomitant preventive drugs) to three 28-day treatment cycles of subcutaneous TEV-48125 675/225 mg (675 mg in the first treatment cycle and 225 mg in the second and third treatment cycles), TEV-48125 900 mg (900 mg in all three treatment cycles), or placebo. Investigators, patients, and the funder were blinded to treatment allocation. Daily headache information was captured using an electronic diary. Primary endpoints were change from baseline in the number of headache-hours during the third treatment cycle (weeks 9–12) and safety and tolerability during the study. Secondary endpoint was change in the number of moderate or severe headache-days in weeks 9–12 relative to baseline. Efficacy endpoints were analysed for the intention-to-treat population. Safety and tolerability were analysed using descriptive statistics. This trial is registered with ClinicalTrials.gov, number, NCT02021773. Findings Between Jan 8, 2014, and Aug 27, 2014, we enrolled 264 participants: 89 were randomly assigned to receive placebo, 88 to receive 675/225 mg TEV-48125, and 87 to receive 900 mg TEV-48125. The mean change from baseline in number of headache-hours during weeks 9–12 was −59·84 h (SD 80·38) in the 675/225 mg group and −67·51 h (79·37) in the 900 mg group, compared with −37·10 h (79·44) in the placebo group. The least square mean difference in the reduction of headache-hours between the placebo and 675/225 mg dose groups was −22·74 h (95% CI −44·28 to −1·21; p=0·0386), whereas the difference between placebo and 900 mg dose groups was −30·41 h (−51·88 to −8·95; p=0·0057). Adverse events were reported by 36 (40%) patients in the placebo group, 47 (53%) patients in the 675/225 mg dose group, and 41 (47%) patients in the 900 mg dose group, whereas treatment-related adverse events were recorded in 15 (17%) patients, 25 (29%) patients, and 28 (32%) patients, respectively. The most common adverse events were mild injection-site pain and pruritus. Four (1%) patients had serious non-treatment-related adverse events (one patient in the placebo group, one patient in the 675/225 mg group, and two patients in the 900 mg group); no treatment-related adverse events were serious and there were no relevant changes in blood pressure or other vital signs. Interpretation TEV-48125 given by subcutaneous injection every 28 days seems to be tolerable and effective, thus supporting the further development of TEV-48125 for the preventive treatment of chronic migraine in a phase 3 trial. Funding Teva Pharmaceuticals.